MANAGEMENT OF THE PRODUCTION PROCESS OF CROP PRODUCTION IN THE OPEN FIELD - О. І. Яковлєв (Ринкова економіка: сучасна теорія і практика управління)
The article formulates the main tasks of constructing a system for managing the process of crop production in the open field based on technologies and tools of operational management, managerial accounting, automation of the collection, transmission and processing of information of process parameters. Ways of solving these problems are determined. The principles of distinguishing operations during the decomposition of the crop production process are proposed.